ARAH POLITIK HUKUM OTONOMI DAERAH (Sebuah Tawaran tentang Model Hukum Humanist Partisipatoris dalam Penyelenggaraan Pemerintahan Daerah yang Otonom) - Zudan Arif Fakrulloh (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
Legal Development is one of the most difficult problems in Indonesia. Two sources of these problems are the pluralism on the social structure and centralistic on making regulation by the government. The “centralistic regulation